Psychiatric Symptoms and Barriers to Care in HIV-Infected Individuals Who Are Lost to Care. (September 2017) - McLean, Carmen P.; Gay, Natalie G.; Metzger, David A.; Foa, Edna B.; ,
Past studies of barriers to HIV care have not comprehensively assessed psychiatric symptoms, and few have assessed barriers to care among people living with HIV (PLWH) who are lost to care (LTC). We examined psychiatric symptoms, barriers to HIV care, and immune functioning in PLWH who were retained in care (RIC; n = 21) or LTC (n = 21). Participants completed diagnostic interviews for posttraumatic stress disorder (PTSD) and other psychiatric disorders, self-report measures of HIV risk behaviors and psychiatric symptoms, and a blood draw to assess viral load. Compared to RIC participants, LTC participants met criteria for a greater number of psychiatric disorders and reported greater depressive symptoms and more barriers to HIV care. There were no group differences in PTSD severity, risk behaviors, or viral load, suggesting that LTC individuals experience greater psychiatric problems and perceive more barriers to care than RIC participants, but are not less likely to have achieved viral suppression.